Research Needs on Conservation of Native Plant Species and Increasing Crop Productivity under Sustainable Agriculture - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
The increased erratic climatic conditions, drought, salinity and other abiotic stresses are affecting bio-resource, native plants, biodivesrsity and crop productivity, thereby threatening food security of the world. With respect to plant species, many native plant species such as cactus, several economic plants such as wild chilli (Chile piquin), lechuguilla, yucca, candelilla, etc. are endangered owing to extensive exploitation for economic benefit of local people. There is a great necessity of the recovery of ethnic knowledge of medicinal plants, inherited from generation to generation since remote past. There is a great necessity of a systematic research, viz., ethnobotany, pharmacognosy, histochemistry, phytochemistry, etc. Very little research is undertaken for conservation and propagation of these native plant species. Techniques have been developed for propagation of 40 cactus species and wild chilli, is a step forward in this direction. Concerted research activities need to be directed in this vital aspect.